Analyses of ionic conductivity and dielectric behavior of solid polymer electrolyte based 2-hydroxyethyl cellulose doped ammonium nitrate plasticized with ethylene carbonate - M N Hafiza; M. I. N. Isa (American Institute of Physics (AIP), 2024)
Indexed by SCOPUS